Operationalizing the Iucn Red List of Ecosystems in Public Policy - Alaniz-Baeza, A (Wiley-Blackwell, 2019)
Threats to ecosystems are closely linked to human development, whereas lack, insufficiency, and inefficiency of public policies are important drivers of environmental decline. Previous studies have discussed the contribution of IUCN s Red List of Ecosystems (RLE) in conservation issues; however, its applications in different policy fields and instruments for achieving biodiversity conservation have not been explored in detail. Here, we introduce a framework to operationalize the RLE in public policy, facilitating work of governments, practitioners, and decision makers. Our analysis identified 20 policy instruments that could reduce risks to ecosystems highlighted by different Red List criteria. We discuss how RLE could inform the policy process by analyzing different instruments that could be designed, implemented, and modified to achieve risk reduction. We also present practical examples from around the world showing how ecosystem conservation could be improved by operationalizing the RLE in policy instruments. The RLE criteria can inform the policy process by helping to shape objectives and identifying policy instruments that directly address the causes and severity of risks illuminated in Red List assessments. We conclude that RLE could be expanded into a broader holistic spectrum of policy instruments, which could be a key to achieving the ecosystem conservation. © 2019 The Authors. Conservation Letters published by Wiley Periodicals, Inc.